Relationship of family role and consumption pattern with gout arthritis disease prevention behavior in geriatri - Ade Rafita Kurniati; Eka Srirahayu Ariestiningsih; Dwi Novri Supriatiningrum (Ghidza Media Jurnal, 2021)
Background: The geriatri are an age group that gets more attention in the world of health, this is because the geriatri are vulnerable to various diseases. One of the diseases that are still widely experienced by the geriatri and still relatively high in Indonesia is gout arthritis or gout. Implementing gout arthritis prevention behavior with encouragement and support from the role of the family, as well as always maintaining the consumption pattern of preventative foods and triggers uric acid can reduce the risk of gout arthritis disease in the geriatri. Aim: To analyze the relationship of family roles and consumption patterns with the prevention behavior of gout arthritis in the geriatri. Method: This research uses quantitative analysis with observational analytical research type and Cross Sectional approach. The research was conducted at the Elderly Police Health Center Manyar Gresik Regency. The population of poly geriatri visitors as many as 88 geriatri. The subjects were taken by 52 seniors using purposive sampling techniques that took into account inclusion and exclusion criteria. The data was collected through interviews using family role questionnaires, FFQ (Food Frequency Questionnare) and gout arthritis prevention behavior. Data analysis using Spearman Rank test, Multiple Correlation test and Multiple Linear Regression test. Results: Based on bivariate analysis with spearman rank test shows that there is a meaningful or significant relationship between family role (p= 0.000), consumption pattern (p< 0.05) with gout arthritis prevention behavior and with multiple correlation test shows that there is a meaningful relationship between family role, consumption pattern with gout arthritis prevention behavior (p= 0.001). Analysis of mulitivariate tests with multiple linear regression tests showed the most influential variable was the role of the family (p= 0.000). Conclusion: There is a relationship between the role of the family and consumption patterns with the prevention behavior of gout arthritis in the geriatri. However, the role of the family is more related to disease prevention behavior in the geriatri. Nutrition education to geriatri patients and their families is very necessary as a source of information to prevent gout arthritis in the geriatri in Gresik Regency Manyar Health Center.